The Self-Concept of Female Adolescents with Acne Vulgaris at Faculty of Nursing Universitas Airlangga Surabaya - Lema, Elizabeth Risha; Yusuf, Ah; Wahyuni, Sylvia Dwi (Psychiatry Nursing Journal (Jurnal Keperawatan Jiwa), 2019)
Introduction: Acne vulgaris is a skin disease that often occurs in adolescence or adulthood. Acne vulgaris can be ensued by many factors, and often leads to scarring or scars that will disrupt the patient's self-concept. At the age of adolescence, especially the late teens, self-actualization will be higher so that with the emergence of the problem of acne vulgaris will greatly affect their self-concept. Thus, it is necessary to conduct a study about the description of the self-concept of young women with acne vulgaris at the Faculty of Nursing Airlangga University SurabayaMethod: This research used qualitative research design of phenomenology approach with in-depth interview method on 15 late adolescent participants and was used field note as guidance. The data analysis used in this study composed into nine steps technique of Colaizzi (1978).Result: The results of this study obtained six themes:  Alteration of body image, maintain individual goal, consistent with individual roles, disturbance of situational low self-esteem, disturbance of chronic low self-esteem, change in self-assessment. Adolescents who have problems with acne vulgaris will feel inferior because of the scar that changes the structure of their skin. Adolescents tend to cover the scars when interacting with other people so that they will have situational low self-esteem problems and even low self-esteem that will change the their assessment of themselves. 4 of the 15 participants continued to play their roles both as students and as adolescents. Adolescents remain active in academic activities and non-academic activities even though they have problems with acne vulgaris.Conclusion: From the results of the study, it is found that not all self-concepts of female adolescents with acne vulgaris are impaired. From the five self-concepts, it is found that adolescents experience a disorder in self-esteem, self-image and their identity. Therefore, the further research is expected to explore more about the extent to which the self-concept of female adolescent who experience disorder.